Rosette-forming glioneuronal tumors share a distinct DNA methylation profile and mutations in FGFR1, with recurrent co-mutation of PIK3CA and NF1 - Sievers, Philipp; Schrimpf, Daniel; Stichel, Damian; Reuss, David; Wefers, Annika K.; Sahm, Felix (Acta neuropathologica, 2019)
Rosette-forming glioneuronal tumor (RGNT) is a rare brain neoplasm that primarily affects young adults. Although alterations affecting the mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K) signaling pathway have been associated with this low-grade entity, comprehensive molecular investigations of RGNT in larger series have not been performed to date, and an integrated view of their genetic and epigenetic profiles is still lacking. Here we describe a genome-wide DNA methylation and targeted sequencing-based characterization of a molecularly distinct class of tumors (n = 30), initially identified through genome-wide DNA methylation screening among a cohort of > 30,000 tumors, of which most were diagnosed histologically as RGNT. FGFR1 hotspot mutations were observed in all tumors analyzed, with co-occurrence of PIK3CA mutations in about two-thirds of the cases (63%). Additional loss-of-function mutations in the tumor suppressor gene NF1 were detected in a subset of cases (33%). Notably, in contrast to most other low-grade gliomas, these tumors often displayed co-occurrence of two or even all three of these mutations. Our data highlight that molecularly defined RGNTs are characterized by highly recurrent combined genetic alterations affecting both MAPK and PI3K signaling pathways. Thus, these two pathways appear to synergistically interact in the formation of RGNT, and offer potential therapeutic targets for this disease.